ANALISIS IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 2 TAHUN 2015 TENTANG KESELAMATAN IBU DAN ANAK DI KOTA SEMARANG - Fara Aulia Oktaviani; Antono Suryoputro; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Regional Regulation of Semarang Number 2 of 2015 on Maternal and Child Safety is a policy to resolved the high of maternal and child mortality rate. The implementation of this policy has not been optimum because midwives in the health facilities have not known about the regulation. The purpose is to analyze the policy implementation of  Regional Regulation on Maternal and Child Safety.The type of this research is descriptive qualitative. The data collection was done through indepth interviews on DKK Semarang, Puskesmas with the lowest and highest mortality rate, and RSUD K.R.M.T Wongsonegoro. The subjects are Head of KIA DKK, midwife coordinator of Puskesmas, and midwife of Hospital, as the main informant and the triangulation ie, Head of Public Health of DKK, Head of Puskesmas, Head of Perinatalogy Inpatient, and policy target. The data analysis using content analysis methods. The variable is  the implementation of Maternal and Child Safety Regulation which seen from the characteristics of the problem, policy characteristics, and environment characteristics.The result shows that the implementation still has constraints on its socialization, due to the dissolution of the information delivery, the method is ineffective, Perwal has not been released yet, and the limited budget. The characteristics of the problems constrained by the perception of health workers have not considered the regulation is effective enough and large target populations complicate the implementation. The characteristic of the policy is hampered by the minimal understanding of health workers about the purpose of the regulation and the lack of midwives. Communication and coordination in the delivery of regulation information has not been optimum because of the low motivation and commitment of Puskesmas to deliver it through meetings. The environmental characteristics are hampered by the socio-economic condition, especially the underprivileged people whose limited at understanding the regulation. Utilization of media in the dissemination of regulation information still minimal. Support of Legal Section is still lacking because it has not prioritized Perwal in its agenda